KONSELING ISLAM DENGAN TERAPI RASIONAL EMOTIF BEHAVIOR UNTUK MENGUBAH WANITA PENYANYI CAFE YANG SUKA MINUM MINUMAN KERAS (Jurusan Bimbingan dan Konseling Islam, 2013)
Social live of female singers Cafe in Bojonegoro supports her habit to drink. This drinking habit is divided into two aspects, namely internal and external aspects. The internal aspects are not rational anymore, so she considers it reasonable to drink liquor. The external aspects that have been affecting the client was friends of the profession and hang out with clients. Counseling process using rational emotive behavior therapy was due to the influence of the association, and because the woman drank alcohol almost every day, but this issue was never aware if she has deviated from social rules and not favored by the people around her. After the Islamic counseling process counselor then find the point of success is marked by changes in activity of women who received counseling prior to this woman every day drinking. After counseling, this women singers Cafe is no longer every day drinking. This woman also change the nature and behavior becoming better. The change of this woman is marked by rarely hang out with people who like to drink liquor, and be a little more rational in thinking.Keywords: Rational Emotive Behavior Therapy, Drinking Liquor Habit